PRINCIPAL TRANSFORMATIONAL LEADERSHIP IN HIGH SCHOOL OF CENTRAL KALIMANTAN - Asti Putri Kartiwi (Universitas Ahmad Dahlan, 2020)
Transformational leadership is considered to play an important role in improving the quality of service because a transformational leader can foster a strong commitment between staff and the organization, as well as staff and teammates where they are willing to work beyond their own abilities for the organization and become potential partners for the organization. This study aims to look at the condition of principals' transformational leadership in state high schools in Central Kalimantan Province with indicators to be seen including Idealized Influenced, Inspiration Motivation, and Intellectual Stimulation. The method used is descriptive quantitative with the teacher as the respondent. Based on the results of the study it is known that the transformational leadership condition of the headmaster of state high schools in the province of Central Kalimantan is in the sufficient category. Suggestions and recommendations are given to school principals to increase intellectual stimulation to subordinates, especially teachers at the school.